PIR-Activated Solar-Powered Variable Ultrasonic Rodent Repellent for Rice Barn - Rizkia Meyliana; Ahmad Taqwa; Suroso (Universitas Muhammadiyah Surabaya, 2026)
Rodent disturbance in traditional rice barns is a post-harvest problem in remote rural villages because stored rice is vulnerable to damage, contamination, and quality degradation. Previous ultrasonic pest-control studies focused on outdoor rice-field environments, whereas rodent control during post-harvest storage in rice barns remains underexplored. This research aims to develop and evaluate a PIR-activated solar-powered variable ultrasonic rodent repellent prototype for rice barn applications. The study employed a Research and Development approach consisting of hardware design, system design, and device evaluation. The prototype integrates Arduino Uno, PIR sensor, ultrasonic speaker, LCD, solar panel, solar charge controller, and 12 V battery. The PIR sensor detects movement and activates ultrasonic output within the 20–100 kHz range. Variable ultrasonic frequency was applied to minimize rodent habituation and identify frequency ranges producing stronger behavioral responses. Testing included solar panel performance, component voltage, PIR sensor distance, and visual observation of rodent behavior. The solar panel produced stable 30 W output, and all components operated effectively at required voltages. The PIR sensor detected movement within 1–3 m, suitable for traditional rice barn areas of 3 × 4 m. Ultrasonic testing identified two sensitivity points within 30–70 kHz, with the strongest response at 70–79 kHz. The prototype is feasible as a non-chemical, energy-independent solution for traditional rice barns.